Collective memory and Spanish cultural politics: the revival of the Roman theatre of Merida (1910–35). (30th June 2020) - Balaskas, Vasileios
Abstract: In the twentieth century, ancient theatres acquired symbolic values through their excavation, restoration, and cultural reuse. While elsewhere in the Mediterranean comparable cases show an early and powerful engagement of a populace with their antiquities, in Spain national ideals did not automatically engage with classical culture. In the case of the Roman theatre of Merida, cultural and historical realities dictated a series of cultural events that repeatedly concerned collective memory. In addition to the main sequence of the unique occasions surrounding the 1933 and 1934 performances at the theatre, various other agencies had systematically focused on its exploitation from the 1910s. These initiatives were endorsed by numerous formal visits and cultural events that took place in the theatre, from as early as 1914. Through successive spectacles staged at the theatre, a cultural tradition emerged, while political agendas occasionally exploited its increasing popularity, right up to the Spanish Civil War.